Intravenous meropenem and intraperitoneal use of 10% aqueous extract of Schinus terebinthifolius Raddi (Anacardiaceae) in elderly rats after induction of autogenous fecal peritonitis - Carlos Alberto Figueiredo Filho; Celia Maria Machado Barbosa de Castro; Guilherme Veras Mascena; Gustavo Ithamar Souto Maior; Tharcia Kiara Beserra Oliveira; Carlos Teixeira Brandt (Acta Cirúrgica Brasileira)
ABSTRACT Purpose: To evaluate intravenous meropenem and intraperitoneal 10% aqueous extract of Schinus terebinthifolius (aroeira) in elderly rats after autogenous fecal peritonitis. Methods: Thirty 18-month-old Wistar rats underwent peritonitis with 4 mL/kg of autogenous fecal solution. They were stratified into groups: control without treatment; study I, treated with meropenem (40 mg/kg); and study II, treated with meropenem at the same dose and intraperitoneal 10% aqueous extract of aroeira. The animals were monitored for 15 days until euthanasia. The study was approved by Ethics Committee. Results: There was no significant weight loss in the study-II group (p = 0.6277), while the study-I group showed partially recovered weight (p = 0.0187). The study-II group had 90% negative blood cultures, while the study-I group had in 50% of the animals (p = 0.1479). Survival in the study-II group was higher than in study-I group (p = 0.0462). The morbidity score for abdominal and thoracic cavity was lower in the study-II group as compared with study-I group (p = 0.0001). Conclusions: The use of meropenem associated with the intraperitoneal 10% aqueous aroeira extract after induction of autogenous fecal peritonitis in elderly rats produced greater survival, less weight loss, and lower morbidity compared to the use of meropenem alone.